What's in a story? Children's learning of new written words via reading experience - Tamura, N (2015)
Over the course of reading development, children are able to recognise an increasingly large number of words by sight, a process termed orthographic learning, as they move from effortful decoding to fast, efficient word recognition. Phonological decoding has been shown to account for some, but not all variance in orthographic learning. While it is clear that reading experience plays a crucial role, the mechanisms underlying orthographic learning require further investigation. The research presented in this thesis had two overarching objectives: first, to establish a novel, sensitive measure of orthographic learning, using the prime-lexicality effect in lexical decision to index the lexicalisation of novel words, and second, to investigate the effects of specific parameters of reading experience on the learning of novel words. In particular, the experiments focussed on incidental, non-directed learning of unfamiliar English words via story reading. Learning was assessed in terms of knowledge of the novel word spellings and meanings themselves, and their engagement with existing words in the lexicon, indexed by the prime-lexicality effect. Five experiments manipulated directed vs. incidental learning, number of exposures, the availability of semantics, and the variability of the story contexts. Across experiments, children showed good learning of the novel words, and a prime-lexicality effect emerged, validating this novel measure. Number of exposures affected lexicalisation of the novel words, as a prime-lexicality effect was evident after twelve exposures, but not after four. Performance was otherwise unaffected by the experimental manipulations, revealing robust orthographic learning in children aged 9 to 11.